An assessment of quality on animated infographics in an Islamic context - Nur Nazihah Rahim; Nik Zulkarnaen Khidzir; Anuar Mohd Yusof; Aznan Zuhid Saidin (2016)
Animated infographics in an Islamic context or also known as animated Islamographics is a new terminology and newbies in the era of Information Communication and Technology (ICT). This kind of infographic can give a bright potential and become an alternative way in understanding and learning Islamic knowledge through creative approach by using simple and attractive design. Unfortunately, a very limited empirical research has been done in this study. This study is meant to explore a critical analysis on the quality of animated Islamographics through assessment of the elements of information, communication and technology. Summative assessment was used to measure and compare the quality of the animated Islamographics between male and female perception. The findings of the research from female perspective shows that the content and message are essential in producing a good animated Islamographics. Whereas, male perspective is more focused on the technical part which is good designing will attract more people to learn Islam through animated Islamographics. Furthermore, the assessment of animated Islamographic on the quality would be used as a preliminary study or the guideline for the next discoveries which are parallel with this research.